The Health Sector Stock Market Reaction to the Implementation of the PSBB Policy Due to Covid-19 in Indonesia - Intan Fadila Rahma; Dyah Pravitasari (INVENTORY: JURNAL AKUNTANSI, 2022)
The pandemic that occurred at the end of 2019 resulted in changes in various sectors of life globally. Indonesia is one of the countries affected by this condition. After the government implemented the Large-Scale Social Restrictions (PSBB), this affected the stock market reaction, especially in the health sector. The research uses a quantitative approach with the type of event study research. This study uses descriptive statistical analysis. In order to test the normality of the data, it is necessary to test for normality using the Shapiro Wilk method. This is because the data used is less than 50. The researcher uses a hypothesis test t Test for data that is normally distributed, while for data that is not normally distributed, it can be tested with the Wilcoxon Signed Ranks Test. The results of this study indicate that before and during the implementation of PSBB, the abnormal return yields were insignificant, and there was no difference between the Average Abnormal Return before and during the implementation of PSBB in the health sector, but the Average Trading Volume Activity showed differences between before and during the implementation of PSBB. when the PSBB was implemented in the health sector. The conclusion is that before and when the PSBB was implemented, it showed that there was no significant difference in the Average Abnormal Return of the health sector, which means that the PSBB did not affect the Average Abnormal Return in the health sector but caused a significant difference in the Average Trading Volume Activity of the health sector, which means that the PSBB had an effect on the Average Trading Volume Activities (ATVA).